2021
DOI: 10.3390/biom11070945
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Metabolism and Parkinson’s Disease—Therapeutic Targets

Abstract: Ceramide is a bioactive sphingolipid involved in numerous cellular processes. In addition to being the precursor of complex sphingolipids, ceramides can act as second messengers, especially when they are generated at the plasma membrane of cells. Its metabolic dysfunction may lead to or be a consequence of an underlying disease. Recent reports on transcriptomics and electrospray ionization mass spectrometry analysis have demonstrated the variation of specific levels of sphingolipids and enzymes involved in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 219 publications
(266 reference statements)
2
29
0
Order By: Relevance
“…Our study clearly indicates the specific accumulation of ceramide species in LBD signifying abnormal sphingolipid metabolism. This observation corroborates other reports of changes in sphingolipid composition of LBD post-mortem tissues [ 18 , 21 ], though decreased ceramide levels have also been reported [ 2 , 64 , 93 ]. Variables such as different anatomical regions, age, mutational profiles, disease duration and/or neuropathological staging might be relevant in understanding these discrepancies [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our study clearly indicates the specific accumulation of ceramide species in LBD signifying abnormal sphingolipid metabolism. This observation corroborates other reports of changes in sphingolipid composition of LBD post-mortem tissues [ 18 , 21 ], though decreased ceramide levels have also been reported [ 2 , 64 , 93 ]. Variables such as different anatomical regions, age, mutational profiles, disease duration and/or neuropathological staging might be relevant in understanding these discrepancies [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…The last step comprises the conversion of glucosylceramide by acid β-glucosidase 1 (β-GCase) to Cer. Dysfunction or deficiency of this enzyme leads to the development of lysosomal storage diseases (LSDs) [ 20 ].…”
Section: Sphingolipid Metabolismmentioning
confidence: 99%
“…When this balance is disturbed or altered, disease may arise. In particular, many inflammatory processes and pathologies, including cardiovascular diseases, neurodegenerative disorders, lung inflammatory disorders (such as chronic obstructive pulmonary disease (COPD) or asthma) type 2 diabetes or cancer, are characterized by disruption of sphingolipid homeostasis [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Moreover, it has been reported that treatment with short-chain Cer anologs is an effective treatment against certain cancers [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Existing pioneering studies of the role of sphingolipids in the molecular mechanisms of PD pathogenesis open up broad prospects for the development of new methods for and the improvement of existing approaches to the diagnosis and treatment of PD. So, recently, the first attempts have been made to translate fundamental knowledge about systemic impairment of sphingolipid metabolism in PD into the development of differential diagnosis and treatment for this disease, based on a search for biomarkers in the body fluids (cerebrospinal fluid and blood) [ 20 , 21 , 22 ]. In addition, it was found that changes in sphingolipid metabolism increase the risk of PD, and correcting sphingolipid levels by regulating the activity of enzymes involved in sphingolipid metabolism can either slow down or prevent the development of this pathology [ 23 ].…”
Section: Introductionmentioning
confidence: 99%